Exploring the interdependence model in Malaysia-Indonesia relations: Insights from Sabah, Malaysia - Ramli Dollah; Amrullah Maraining; Adi Jafar; Eko Prayitno Joko; Nordin Sakke (Kulliyyah of Islamic Revealed Knowledge and Human Sciences International Islamic University Malaysia, 2024)
The historical similarities between Malaysia and Indonesia, apparent in geographical proximity and social-cultural dimensions, significantly influence perspectives and discourse on their bilateral relations. Despite frequent assertions of shared kinship and racial ties, relations between Malaysia and Indonesia are consistently characterised by rivalry, marked by numerous disagreements and challenges. This paper posits that conflict is a minor element in the broader discourse of relations, emphasising the importance of cooperation due to the complex interdependence between these two countries. Using Sabah as a case study, this paper highlights the significance of interdependence between Malaysia and Indonesia, delving into pivotal issues that shape the dynamics of their bilateral relationship. It focuses on several issues such as the population and kinship ties, the reliance of the Sabah economic sector on the Indonesian Migrant Workers (PMI), consumer goods and everyday necessities, interdependence in the security sector, and finally haze and environmental pollutions to outline the dynamics of interdependence between Sabah (Malaysia) and Indonesia. All facets describing these relations are emphasised since they demonstrate that these two countries are interdependent and share common interests in nearly all sectors. This paper contends that despite facing various contentious issues and problems, the interdependence that occurs contributes to a harmonious relationship and is able to avoid conflict between the two countries.